Wykładnia pojęcia „dobrej wiary” w orzecznictwie w kontekście dokonywanych w okresie PRL naruszeń prawa własności - Gołębiowski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article aims to asses the jurisprudence of the first decades of the 21st century regarding the good faith of state-owned enterprises that began, without a legal title, to use private land in the communist period, placing on them the infrastructure used to transmit electric energy. Courts interpreting general clauses referring to concepts and systems of values lying outside the legal system gain the ability to influence the decision of the case based on their own moral judgments. Therefore, the case where Polish courts operating in a state that respects the principle of equal property protection regardless if the entitled entity had the opportunity to assess the conduct of entities representing the state operating on the basis of a completely different system of values, should be considered particularly interesting. It is typical for totalitarian and authoritarian regimes to formally grant broad protection to individual rights and, at the same time ignore their existence in the activities of the state. It can be seen in the practice of carrying out some infrastructure investments in the communist period. Electricity networks were often built on private land. At that time, there were regulations allowing to obtain a legal title to use the land, both in private law (contract) and of an administrative (expropriation) nature. The state and state-owned enterprises, however, mostly did not use them, focusing on planning investments to obtain permits related to technical issues. The reasons for this behavior can be seen primarily in the basic assumptions of the socialist system. The described practice testified to the real attitude of the state to private property as a type of property that was ultimately to be ousted in the socialist system. The role of economic plans in the Polish People’s Republic was also significant. State bodies and state-owned enterprises primarily aimed at executing plans, regardless of whether or not they violated the individual’s interests in this way. After 1989, the legal status of many power grids, overhead lines, and other devices was therefore not regulated. State-owned enterprises, and the companies resulting from their transformation, used many properties without a legal title. Changes in the legal awareness of society and the growing understanding of economic mechanisms based on the principles of responsibility for one’s own actions and protection of subjective rights, led to many court disputes between owners and entrepreneurs. The most common claims addressed to transmission companies were remunerations for the use of land without legal title and actio negatoria. The case law reacted to the increase in the number of disputes by creating a concept of usucaption of land easement for the benefit of the transmission entrepreneur. Its legitimacy from the beginning raised fundamental doubts in the legal doctrine, but it gained the full support of the courts. Many statements of the Supreme Court assessed the correctness of the state-owned enterprises’ conduct. The relatively numerous statements approving the omission of obtaining a legal title to seize someone else’s real estate in the investment preparation process ought to be considered interesting and surprising. They significantly influenced the practice of common courts, causing many claims of property owners against entrepreneurs to be dismissed. Moreover, by expressly praising unlawful interference with the right to property, carried out during the Polish Peopleʼs Republic, they probably also deepened the sense of harm and injustice — caused mainly by a surprising interpretation that allowed for the acquisition by prescription of a right unknown to the Act — and above all the belief that courts treated trade participants unequally and that courts granted significant privileging to the state and entities representing its interests.
Keywords: dobra wiara (prawo); prawo własności w ustroju autorytarnym; nabycie prawa przez zasiedzenie